Dietary chromium supplementation for heat-stressed broilers. Issue 1 (1st March 2018) - Dalólio, F.S.; Albino, L.F.T.; Silva, J.N.; Campos, P.H.R.F.; Lima, H.J.D.; Moreira, J.; Ribeiro Junior, V.
Abstract : Studies have shown that dietary chromium (Cr) supplementation beneficially affects physiological functions such as cell preservation, antioxidant activity and immune response that are of utmost importance to animal homeostasis and thermoregulatory capacity under heat stress conditions. For instance, Cr is essential for the synthesis of the specific low molecular weight Cr-binding-substance (LMWCr) that upon conversion to chromodulin, activates the insulin signalling cascade. This results in greater cell permeability to insulin, with a subsequent positive effect on the metabolism of carbohydrates, lipids and proteins. Furthermore, Cr has antioxidant properties which help to attenuate the negative effects of oxidative stress. With regards to meat quality, Cr decreases lipid peroxidation. It has been suggested that Cr supplementation increases antibody responses and lymphocyte counts in broiler chickens exposed to high environmental temperatures. In addition, trivalent Cr supplementation increases growth performance and decreases the circulating levels of undesirable metabolites and hormones such as cholesterol and corticosterone in broiler chickens exposed to heat stress. The aim of this review was to report the effects of Cr supplementation as a nutritional strategy to increase growth performance, immune response, carcass characteristics and meat quality of broilers produced under hot conditions. This knowledge may contribute to improve the productivity and sustainability of broiler production in a context of global warming and development of livestock production in hot climate areas.